Evidence-based approaches to health risk mitigation and value creation in U.S. livestock production systems - de Aguiar Veloso, Vanessa (My University, 2025)
The U.S. livestock industry faces increasing pressure to balance productivity, economic efficiency, and sustainability while minimizing disease risks, antimicrobial use, environmental impacts, and animal welfare concerns. This dissertation applies epidemiological and economic principles to enhance evidence-based decision-making for managing agricultural risks across diverse livestock systems. Agricultural risks are commonly categorized as financial, institutional, human resources, market, and production risks. Yet, effective management goes beyond objective classifications; it also requires an understanding of how producers and other stakeholders perceive and interpret these risks. Perceptions shape how risks are prioritized, and which management strategies are adopted, influencing outcomes at both the farm and industry levels. Outcomes research provides a framework for integrating scientific evidence with practical decision-making in livestock systems. By applying clinical and population-based methods to evaluate the effectiveness and value of interventions, it bridges the gap between research and practice, reduces uncertainty, and strengthens the producers’ capacity to manage agricultural risks through informed, evidence-based strategies. These concepts are described and discussed in Chapter 1. Chapter 2 is a rapid systematic review synthesizing knowledge on the role of swine in the transmission dynamics of Japanese encephalitis virus (JEV), diagnostic methods, and preventive and surveillance strategies. The review highlights key data gaps in the potential role of feral swine in JEV transmission, identifying priorities for U.S. surveillance and preparedness to mitigate the risk of JEV introduction and establishment. A survey design was employed in Chapter 3 to characterize veterinarian and feedlot manager perceptions and decision-making considerations regarding metaphylaxis use for cattle at moderate risk of bovine respiratory disease. The study identifies both alignment and divergence in how disease risk, information access, and management priorities influence antimicrobial use, underscoring opportunities to improve communication and support antimicrobial stewardship within feedlot systems. In Chapter 4, observational auction market data were used to evaluate the economic impact of value-added management programs on feeder calf sale prices. Through regression modeling, the study estimates price premiums associated with specific program combinations and illustrates how information asymmetries may influence market efficiency and producer decision-making capacity. Together, these studies emphasize the central role of information — derived from diverse data sources and research approaches — in improving disease risk management and supporting sustainable livestock production. With them, the need for continued investment in data integration, traceability systems, and communication frameworks that enhance transparency (or information access) and evidence-based practice is highlighted. Strengthening information networks will be essential for improving efficiency and profitability, adapting to evolving societal values, and ultimately promoting the resilience of U.S. livestock systems.
Keywords: Agricultural risks; Outcomes research; Japanese encephalitis virus; Bovine respiratory disease; Metaphylaxis; Value-added programs